2005
DOI: 10.1038/sj.eye.6702150
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology in paediatric aphakic glaucoma

Abstract: Purpose To investigate the causes of glaucoma in children following removal of cataracts. Methods In total, 24 patients (37 eyes) with uncomplicated congenital cataracts who developed glaucoma following cataract removal were studied retrospectively. Cataract morphology, surgical technique, postoperative complications, time to glaucoma onset, gonioscopic findings, the presence of microcornea, and the histopathologic characteristics of the filtration angle in one case were the studied parameters. Results We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…First, our mean follow-up was short compared with other studies, where the mean follow-up was higher than 5 years 4 10 33. Also, the improvement in surgical techniques (smaller incisions, decreased surgical time, posterior capsulotomy with anterior vitrectomy, use of foldable IOL at earlier ages)8 31 34 may have reduced the incidence of postoperative complications, including glaucoma.…”
Section: Discussionmentioning
confidence: 87%
“…First, our mean follow-up was short compared with other studies, where the mean follow-up was higher than 5 years 4 10 33. Also, the improvement in surgical techniques (smaller incisions, decreased surgical time, posterior capsulotomy with anterior vitrectomy, use of foldable IOL at earlier ages)8 31 34 may have reduced the incidence of postoperative complications, including glaucoma.…”
Section: Discussionmentioning
confidence: 87%
“…Surgery during the first year of life is thought to increase the risk of glaucoma,3 5 16 and so this cohort is a high risk eyes for development of glaucoma. Previous studies indicate a bimodal aphakic glaucoma onset:4 11 15 with early glaucoma presenting within the first year after lensectomy significantly associated with angle closure, and a late open-angle glaucoma occurring much later,11 15 but not all these studies were restricted to infants.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 29 the incidence of glaucoma was 24.4% in pseudophakic eyes and 19.0% in aphakic eyes. Koc et al 30 report bimodal onset of glaucoma, with early-onset glaucoma occurring at a mean age of 6 months (likely resulting from angle closure) and delayed-onset glaucoma at a mean age of 12 years (in 86%, resulting from an open filtration angle). Chen et al 28 found an open angle in 93.9% of cases of aphakic glaucoma.…”
Section: Discussionmentioning
confidence: 99%